Hydroxyalkylation–alkylation of biomass-derived furanics toward sustainable aviation fuel production: Reaction pathways, catalysts and design strategies - Feri Mukhayan; Muhammad Yusril Baihaqi; Muhammad Al Muttaqii; Muhammad Ridwan; Indri Yati (Bioresource Technology Reports, 2026)

Phytochemistry, preclinical pharmacology, quality control, and translational perspectives of Daemonorops draco (Dragon’s blood) - Anjar Purba Asmara; Clerance Su Yee Cheong; Muhammad Ridwan Harahap; Tewin Tencomnao; Anchalee Prasansuklab (Phytochemistry Reviews, 2026)

A review of yellowfin tuna ecology in a changing ocean: Synthesis of habitat dynamics, oceanographic influences, and climate impacts (1963–2023) - Siti Khadijah Srioktoviana; Mukti Zainuddin; Rachmat Hidayat; Alfira Yuniar; Aisjah Farhum; Safruddin; Muzzneena Ahmad Mustapha; Andi Risda Fitrianti Abudarda; Muhammad Ridwan (Regional Studies in Marine Science, 2026)

In silico identification of GTPase inhibitors from selected anti-gonorrheal plants against Neisseria gonorrhoeae - Blessing O. Awoyemi; Badmus Jamiu Damilare; Abdullahi Tunde Aborode; Che Muhammad Khairul Hisyam Ismail; Abdulqohar Adebayo; Haruna Isiyaku Umar; Ibrahim Akindeji Makinde; Ridwan Opeyemi Bello; Sodiq Fakorede; Mohammed M. Alshehri; Ahmed F. Alanazi (The Nucleus, 2025)

Tenofovir and levonorgestrel vaginal MPT film developed via quality by design approach (drug release and safety evaluation in an animal model) - Ridwan Muhammad; Peace-OfonAbasi O. Bassey; Solomon C. Nwaneri; Ibilola M. Cardoso-Daodu; Afusat A. Oladosu; Karamot O. Oyediran; Margaret O. Ilomuanya (Next Research, 2025)

Detection of genes encoding for absorption of hydrocarbons degradation by bacteria isolated from Antarctica, Malaysia, and Indonesia - Faisal Allafi; Muhammad Ridwan; Peter Convey; Dani Wijaya; Faradina Merican; Japareng Lalung (Next Research, 2025)

Ameliorative Effect of Rauwolfia vomitoria Ethanol Extract on the Erectile Dysfunction Complicated with Coronary Artery Disease: An In-Vivo and Molecular Docking Approach - Hamdalat Folake Muritala; Ridwan Ayinla Abdulrahman; Habeebat Adekilekun Oyewusi; Hashim Ndaman Muhammad (Cell Biochemistry and Biophysics, 2025)

Alteration of the gut microbial composition of critically endangered Malayan tigers (Panthera tigris jacksoni) in captivity during enrichment phase - Mohamad Khairulmunir; Millawati Gani; Abd Rahman Mohd-Ridwan; Kayal Vizi Karuppannan; Muhammad Abu Bakar Abdul-Latiff; Badrul Munir Md-Zain (Molecular Biology Reports, 2024)

Incorporating Halal Into Healthy and Equitable Dietary Patterns to Address Food and Nutrition Security Among K-12 and University Students: A Perspective - Amelia Keleher; Meira Neggaz; Christine M. Cliff; YaQutullah Ibraheem Muhammad; Anne Mathews; Habeeb Quadri; Ridwan Abdul Rashid; Nadeem Zafar; Asma Ahad (Journal of Nutrition Education and Behavior, 2024)

Maximizing energy via solar‐powered smart irrigation: An approach utilizing a single‐axis solar tracking mechanism - Firas Basim Ismail; Muhammad Aqil Afham Rahmat; Hussein A. Kazem; Abdulkareem Sh. Mahdi Al‐Obaidi; Muhammad Syauqi Ridwan (Irrigation and Drainage, 2024)
This study presents and assesses the novelty of a cutting‐edge solar‐powered automated irrigation system that incorporates a single‐axis solar tracker. The research entails the meticulous development of a prototype, followed by comprehensive experimental scrutiny spanning 3 days, from 8:00 AM to 6:00 PM. In a unique approach, we benchmark the findings against previous research endeavours, highlighting the transformative potential of our innovative design. Our innovative system harnesses a singular‐axis solar tracking mechanism alongside moisture sensors and a water pump relay module, resulting in the creation of an autonomous irrigation system perpetually powered by solar energy. The results are noteworthy, showcasing the capability of a solar panel equipped with single‐axis tracking to significantly boost photovoltaic output power. This configuration attains a remarkable 65% increase in total output power and a substantial improvement over the modest 52%–53% performance of fixed solar panels. This substantial divergence translates to a noteworthy 12%–13% difference in efficacy, underscoring the pioneering nature of our research. The zenith of power output, ranging between 3.16 and 3.68 W, transpires from noon to 2:00 PM, further illustrating the system's viability. The integrated water pump exhibits commendable efficiency, attaining levels as high as 75%. This revelation underscores the transformative potential of automated irrigation systems endowed with single‐axis solar tracking technology, auguring amplified system performance and heralding a new era of sustainable agricultural practices.

Neutralizing the surging emissions amidst natural resource dependence, eco-innovation, and green energy in G7 countries: Insights for global environmental sustainability - Rabia Akram; Ridwan Lanre Ibrahim; Zhen Wang; Tomiwa Sunday Adebayo; Muhammad Irfan (Journal of Environmental Management, 2023)

Pyrethroid residues in Indonesian river Citarum: A simple analytical method applied for an ecological and human health risk assessment - Miranti Ariyani; Retno Yusiasih; Een Sri Endah; Tiny Agustini Koesmawati; Yohanes Susanto Ridwan; Oman Rohman; Diana Rahayuning Wulan; Muhammad Bachri Amran; Mariska Margaret Pitoi (Chemosphere, 2023)

Hexavalent chromium contamination in groundwater and its implication to human health: a Monte Carlo model approach in Indonesia - Ratna Dwi Puji Astuti; Anwar Mallongi; Ridwan Amiruddin; Muhammad Hatta; Annisa Utami Rauf (Sustainable Water Resources Management, 2023)

From knowledge to action: multi-stakeholder planning for urban climate change adaptation and resilience in the Asia–Pacific - Micah R. Fisher; Keith A. Bettinger; Kem Lowry; Muhammad Ridwan Lessy; Wilmar Salim; Dolores Foley (Socio-Ecological Practice Research, 2022)